Murder reflected in robert galbraith's the cuckoo's calling (2013: A psychoanalytic approach - Zahra B, Nana Shabihah; , Dr. Phil. Dewi Chandraningrum, M. Ed (2016)
The major problem of this study is murder. It shows the desire to kill for the obsession of money. The approach used for this study is psychoanalytic approach. The objective of this study is to analyze this novel based on the Psychoanalytic Approach. The research employs qualitative research. The research uses two data sources: primary and secondary. The primary data source of the study is The Cuckoo's Calling novel by Robert Galbraith. Secondary data are the supporting data taken from literary books, internet, and some articles related to the novel. The method of data collection is the researcher will employ the descriptive qualitative research. Using a psychoanalytic approach as the theoretical framework: First, based on the structural analysis, John Bristow delivers a message that unnatural obsession can cause effect to another people such as murder. Second, based on psychoanalytic analysis John wants to convey the psychological phenomena that is a type personality that leads to murderer.